Connecting with Deities: The Practice of Spirit Mediumship among the Chinese in Kuantan, Pahang - Melvin Foo Bok Yee; Elena Chai (Kajian Malaysia, 2021)
The belief towards the spirit medium is one of the oldest beliefs in Chinese folk religion. This research explored spirit mediumship practices among the Chinese in Kuantan, Pahang, and interviewed 10 spirit mediums by applying interpretive phenomenological analysis. The findings indicate that the ability to interact with deities is either due to unavoidable illness, hereditary, naturally acquired, or learned. Indeed, a spirit medium may or may not convey messages to the audience or the deities from ritual performances. However, the ritual had revealed an “indispensable and official” status among mediums and worshippers. Although some expectations of this practice have faded due to modernity, it is still popular among the Chinese, especially in bonding the Chinese together as one community.